Front Cover: Cu Atomic Chain Supported on Graphene Nanoribbon for Effective Conversion of CO2 to Ethanol (ChemPhysChem 16/2020). Issue 16 (24th August 2020) - Shen, Haoming; Sun, Qiang
Abstract : The Front Cover shows how a Cu‐decorated zigzag graphene nanoribbon is capable of catalyzing CO2 reduction to ethanol with a small energy barrier and tunable selectivity. More information can be found in the Article by Haoming Shen and Qiang Sun .